Identification of social mechanisms with the use of actor-centred institutionalism - Krupnik, Seweryn (Journal of Public Governance, 2014)
The article summarizes a research project whose aim was to identify the mechanism of public subsidies. It aims to present the theoretical frameworks of the research project, which were designed on the basis of actor-centred institutionalism. The frameworks made it possible not only to achieve the main aim of the project but also to identify the dysfunctional features of the intervention and the mechanism accounting for the permanence of the public subsidies.